2020
DOI: 10.1109/access.2020.2978090
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Shape Classification System Based on Multi-Channel CNN and Improved FDM

Abstract: This paper presents a new meteorological photo classification system based on the Multichannel Convolutional Neural Network (CNN) and improved Frame Difference Method (FDM). This system can work in an embedded system with limited computational resources and categorize cloud observation photos captured by ground cameras. We propose the improved FDM extractor to detect and extract cloudlike objects from large photos into small images. Then, these small images are sent to a Multi-channel CNN image classifier. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 26 publications
0
61
0
Order By: Relevance
“…With the development of data information technology such as big data and machine learning [28,29], using data algorithms to mine valuable information from large amounts of data has become a hot topic of data research [30,31]. e sports health application, which collects a large number of users' sports and physical signs data, can use data information technology to dig out valuable information, so that the sports assistant service can be more intelligent and personalized.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of data information technology such as big data and machine learning [28,29], using data algorithms to mine valuable information from large amounts of data has become a hot topic of data research [30,31]. e sports health application, which collects a large number of users' sports and physical signs data, can use data information technology to dig out valuable information, so that the sports assistant service can be more intelligent and personalized.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we used the NeuralNetTools package ( Beck, 2018 ) to obtain the relative importance (weight) of input variables (smile, eye contact, gesture, and tone) in the neural network ( Zhao et al, 2020 ; Chu et al, 2021 ; You et al, 2021 ; Zhang et al, 2021 ) through garson algorithm ( Ghanizadeh et al, 2020 ). As shown in Figure 3 , it can be found that the foreign language teacher’s eye contact and gesture have a greater influence on the decision of whether to improve students’ classroom learning efficiency (the weight of each variable is above 30%), followed by tone and smile (the weight of each variable is between 10 and 20%).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…e realization of high-precision cost forecasting through mathematical modeling has piqued the interest of industry professionals and academics [21,22], thanks to the rapid advancement of computer and neural network technologies [23][24][25]. Certain mathematical models and related historical engineering data are used to make the construction cost forecast.…”
Section: Introductionmentioning
confidence: 99%